Τheoretical study of the 13C + d system, in the framework of the R-Matrix model - Kyritsis, Nikolaos; Kokkoris, Michalis (HNPS Advances in Nuclear Physics, 2023)
In the present work, a theoretical study of the 13C + d system is carried out in the framework of the R-Matrix model. The experimental data used were taken from the IBANDL library. The cross-section measurements for the reactions have been carried out in the energy range of 0.49-1.65 MeV for three backscattering angles of 135°, 150° and 165°. The R-Matrix calculations were performed with the use of the AZURE2 code and involved the simultaneous analysis of the 13C (d, p0)14C, 13C (d, t0)12C 13C (d, a0)11B, 13C(d,a1)11B reaction channels with one, coherent set of parameters.